The Influence Of Work Culture, Social Concern, And Organizational Commitment On Employee Performance Improvement With Job Satisfaction As A Mediation - Rahmawati Rahmawati; Cynthia Friska Ayuningsih; Gita Sugiarti (International Journal of Economics and Management Research, 2023)
This research aims to assess and analyze the impact of work culture, social concern, and organizational commitment on enhancing employee performance at the Regional Financial Management Board of Pekalongan Regency. The study adopts a quantitative approach, specifically causal associative research. The variables considered include work culture, social concern, and organizational commitment, while employee performance improvement is the dependent variable. The sample comprises 88 employees from the Regional Financial Management Board of Pekalongan Regency. Data collection is carried out using a questionnaire. The collected data undergoes statistical analysis, including validity and reliability tests for the questionnaire instrument. The path analysis is conducted, and before that, classical assumption tests, such as normality, multicollinearity, and heteroscedasticity, are performed using SPSS ver. 24.